Cyber-Epicurean Food Marketing: A Conceptual Model of Business Resource Structuring for SMEs in the Digital Era - Chavid Moyo Jaladri; Agus Wisatono (Equity: Jurnal Ekonomi, 2026)
This study investigates the influence of sensory experience (SE), satiety value (SV), menu selection (MS), hygiene (HYG), and price (PRC) on customer satisfaction (CS) and customer loyalty (CL) within the context of small and medium-sized culinary enterprises. Using regression analysis, the findings reveal that MS and HYG are the dominant predictors of CS, while SE, SV, and PRC also contribute positively, though to a lesser extent. CS is confirmed as a strong predictor of CL, highlighting that higher satisfaction directly fosters repeat patronage and positive word-of-mouth. However, the introduction of cyber marketing (CM) shows a negative direct effect on CL and no moderating influence on the CS–CL relationship, indicating that current digital marketing strategies remain insufficient in strengthening loyalty. These results emphasize the importance of enhancing core service quality dimensions, particularly menu variety and hygiene, while redesigning digital marketing initiatives to complement customer experiences and build sustainable loyalty.